"Worth the Walk": Culturally Tailored Stroke Risk Factor Reduction Intervention in Community Senior Centers. Issue 6 (19th March 2019) - Menkin, Josephine A.; McCreath, Heather E.; Song, Sarah Y.; Carrillo, Carmen A.; Reyes, Carmen E.; Trejo, Laura; Choi, Sarah E.; Willis, Phyllis; Jimenez, Elizabeth; Ma, Sina; Chang, Emiley; Liu, Honghu; et al.
Abstract : Background: Racial/ethnic minority older adults have worse stroke burden than non‐Hispanic white and younger counterparts. Our academic‐community partner team tested a culturally tailored 1‐month (8‐session) intervention to increase walking and stroke knowledge among Latino, Korean, Chinese, and black seniors. Methods and Results: We conducted a randomized wait‐list controlled trial of 233 adults aged 60 years and older, with a history of hypertension, recruited from senior centers. Outcomes were measured at baseline (T0), immediately after the 1‐month intervention (T1), and 2 months later (T2). The primary outcome was pedometer‐measured change in steps. Secondary outcomes included stroke knowledge (eg, intention to call 911 for stroke symptoms) and other self‐reported and clinical measures of health. Mean age of participants was 74 years; 90% completed T2. Intervention participants had better daily walking change scores than control participants at T1 (489 versus −398 steps; mean difference in change=887; 97.5% CI, 137–1636), but not T2 after adjusting for multiple comparisons (233 versus −714; mean difference in change=947; 97.5% CI, −108 to 2002). The intervention increased the percent of stroke symptoms for which participants would call 911 (from 49% to 68%); the control group did not change (mean difference in change T0–T1=22%; 99.9% CI, 9–34%). This effect persisted at T2. The intervention did not affect measures of health (eg, blood pressure). Conclusions: This community‐partnered intervention did not succeed in increasing and sustaining meaningful improvements in walking levels among minority seniors, but it caused large, sustained improvements in stroke preparedness. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02181062.